Pengaruh Algoritma Facebook terhadap Polarisasi Politik di Kota Medan Selama Pemilu 2024 - Siti Maisaroh; Silvy Novianty; Shalsabyla Finta Azalea (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
This study analyzes the impact of Facebook's algorithm on political polarization in Medan during the 2024 elections. Facebook's algorithm is designed to personalize content based on user interactions and preferences, which can create echo chambers and filter bubbles, reinforcing existing political beliefs and reducing openness to different viewpoints. Using a mixed-method approach that includes content analysis and user surveys, this research explores how content recommendation algorithms influence user interactions, the dissemination of political information, and the formation of polarized social groups. The findings show that Facebook's algorithm significantly contributes to political polarization in Medan during the 2024 elections. Recommendations to mitigate the negative effects of political polarization are also presented, including policies and practices for more mindful management of social media algorithms.